VD_FINDINFO AI 73/10 - 470/2011 vom 24. Oktober 2011 - VD Tribunal cantonal (2011)
DEGRÉ DE L'INVALIDITÉ, LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ, RENTE D'INVALIDITÉ | 28 LAI, 8 LAI, 6 LPGA, 7 LPGA, 8 LPGA